Harmonic self‐mode‐locking of optically pumped semiconductor disc laser. Issue 7 (1st March 2014) - Gaafar, M.; Möller, C.; Wichmann, M.; Heinen, B.; Kunert, B.; Rahimi‐Iman, A.; Stolz, W.; Koch, M.
Abstract : A saturable‐absorber‐free vertical‐external‐cavity surface‐emitting laser is presented which is harmonically modelocked. Modelocking is initiated via fine‐tuning of an aperture which is placed near one of the cavity's end mirrors. Fundamental modelocking is observed along with the second and third harmonic operations for increased optical pump powers. The system features pulse durations penetrating the femtosecond regime at a wavelength of 1014 nm.